"War Landscape” of Kurt Lewin: reasons and ways of quest for own methodology - Zeidler, Włodzisław (Studia Psychologica: Theoria et praxis, 2009)
In this article the author presents and argues the view that “War Landscape” of Kurt Lewin, in the intention of himself was not the war report. The earlier works of Lewin - little known - reveal his consistent quest of work out the own methodology of scientific study which was begun when he was a student and which was based on neokantist assumptions (J. Cohn, A. Riehl, P. Natop, E. Cassirer). The keystone of this methodology becomes the concept of situation. In “war landscape” Kurt Lewin uses “the war” as an instrument which serves to show and to understand better, what the situation is, as a scientific concept.